The Role of Digital Rectal Examination for Diagnosis of Acute Appendicitis: A Systematic Review and Meta-Analysis. - Toshihiko Takada; Hiroki Nishiwaki; Yosuke Yamamoto; Yoshinori Noguchi; Shingo Fukuma; Shin Yamazaki; Shunichi Fukuhara (PLoS ONE, 2015)
Background Digital rectal examination (DRE) has been traditionally recommended to evaluate acute appendicitis, although several reports indicate its lack of utility for this diagnosis. No meta-analysis has examined DRE for diagnosis of acute appendicitis. Objectives To assess the role of DRE for diagnosis of acute appendicitis. Data sources Cochrane Library, PubMed, and SCOPUS from the earliest available date of indexing through November 23, 2014, with no language restrictions. Study selection Clinical studies assessing DRE as an index test for diagnosis of acute appendicitis. Data extraction and synthesis Two independent reviewers extracted study data and assessed the quality, using the Quality Assessment of Diagnostic Accuracy Studies 2 tool. Bivariate random-effects models were used for the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio (DOR) as point estimates with 95% confidence intervals (CI). Main outcomes and measures The main outcome measure was the diagnostic performance of DRE for diagnosis of acute appendicitis. Results We identified 19 studies with a total of 7511 patients. The pooled sensitivity and specificity were 0.49 (95% CI 0.42-0.56) and 0.61 (95% CI 0.53-0.67), respectively. The positive and negative likelihood ratios were 1.24 (95% CI 0.97-1.58) and 0.85 (95% CI 0.70-1.02), respectively. The DOR was 1.46 (0.95-2.26). Conclusion and relevance Acute appendicitis cannot be ruled in or out through the result of DRE. Reconsideration is needed for the traditional teaching that rectal examination should be performed routinely in all patients with suspected appendicitis.